The Gothic line : Canada's month of hell in World War II Italy - Zuehlke, Mark, 1955- (Douglas & McIntyre, 2003)
Stretching like an armor-toothed belt across Italy's upper thigh, the Gothic Line was the most fiercely defended position of Hitler's army, but a bloody 28-day offensive led by Canada's first Infantry Division ruptured the German defenses and opened the way for an Allied advance. Through the vivid stories of the soldiers who fought there, this dramatic book recounts a forgotten part of Canadian history and captures the horror and glory Canadians found on the remote battlefield of a far-off land.